Evaluation of bone resorption in fibula and deep circumflex iliac artery flaps following dental implantation: A three-year follow-up study. Issue 4 (April 2017) - Kniha, Kristian; Möhlhenrich, Stephan Christian; Foldenauer, Ann Christina; Peters, Florian; Ayoub, Nassim; Goloborodko, Evgeny; Hölzle, Frank; Modabber, Ali
Abstract: Long-term results of dental implant treatment in fibula free and deep circumflex iliac artery (DCIA) free flaps are scarce. The purpose of this study was to assess and compare peri-implant bone resorption of vascularized bone flaps treated with dental implants. A total of 28 patients, 14 fibula and 14 DCIA flaps, respectively, underwent reconstruction of the lower and upper jaw by the use of vascularized bone flaps and were treated with dental implants. Peri-implant bone resorption was measured using digital panographs up to 3 years. Radiographic pictures were taken immediately after implant surgery before prosthetic rehabilitation (T0), the second after 6–12 months (T1), the third after 13–24 months (T2), and the fourth after 25–36 months (T3). Over a period of 3 years, implant resorption changed significantly over time (pD1 = 0.0113, pD2 = 0.0232, pD3 = 0.0143). However, a significant difference in overall resorption between implants with fibula flaps and DCIA could not be detected for the patient average or within the implant-level analysis. Flaps presented minimal resorption from beneath (mean resorption DCIA 0.65, fibula = 0.26). Strong peri-implant bone resorption changed significantly over time. However, no significant difference was observed between fibula and DCIA flaps.